2000
DOI: 10.1063/1.1318937
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of excimer-laser-annealed polycrystalline silicon films grown by ultrahigh-vacuum chemical vapor deposition

Abstract: Polycrystalline silicon (poly-Si) films grown by ultrahigh-vacuum chemical vapor deposition (UHVCVD) system and then annealed by excimer laser at room temperature have been investigated for the applications in polycrystalline silicon thin-film transistors (poly-Si TFTs). The results showed that the grain size of the laser-annealed poly-Si film decreased with laser energy density when a lower laser energy density below 157.7 mJ/cm2 was used. At about the threshold laser energy density (∼134.5 mJ/cm2), the fines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In the poly-Si films crystallized by conventional ELA, a prominent ridge was formed at a grain boundary owing to the stress concentration. 13 Thus, it is expected that crystal strain is easily caused near grain boundaries. Therefore, we concluded that hydrogen termination does not randomly progress, and there are regions that cannot be easily inactivated near grain boundaries.…”
Section: Characterization Of Local Electrical Properties Of Polycrystmentioning
confidence: 99%
“…In the poly-Si films crystallized by conventional ELA, a prominent ridge was formed at a grain boundary owing to the stress concentration. 13 Thus, it is expected that crystal strain is easily caused near grain boundaries. Therefore, we concluded that hydrogen termination does not randomly progress, and there are regions that cannot be easily inactivated near grain boundaries.…”
Section: Characterization Of Local Electrical Properties Of Polycrystmentioning
confidence: 99%
“…Among these three processes, ELA of a-Si films appears to be very promising due to its lower thermal budget, shorter processing time, and ability to produce poly-Si films with better quality. 4 However, the equipment cost is high. As for the SPC method, it is a well-established poly-Si formation technique with several advantages over ELA, including smoother surfaces, better uniformity, and the use of the batch process in furnace annealing.…”
Section: Introductionmentioning
confidence: 99%
“…However, this method was not compatible for display device process because it usually need a high temperature (>700 ℃) [3][4]. Excimer laser annealing (ELA) is promising method for a low temperature fabrication process upon illumination of laser pulses, amorphous silicon film was melted and re-crystallized as the poly crystalline silicon film [5][6]. Thus, Si QDs could be nucleated and crystallized in silicon-rich silicon nitride (SRSN) film by using ELA.…”
mentioning
confidence: 99%